2021
DOI: 10.1038/s41598-021-85330-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home quarantine during COVID-19 lockdown on physical activity and dietary habits of adults in Saudi Arabia

Abstract: Public health endorsements during the present COVID-19 pandemic has led the governments of largely affected countries to imply policies that restrict social mobility to slow COVID-19 spread. The study aimed to explore the effects of COVID-19 home quarantine on lifestyle and health behavior of Saudi residents. An online survey in Saudi Arabia was launched from May 11 to June 6, 2020. The survey was designed by multidisciplinary scientists and academics uploaded and shared through the Google platform in Arabic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 32 publications
3
85
2
8
Order By: Relevance
“…However, the findings contraindicated the results of the previous study showing the negative effect of home quarantine on physical activity among adults in Saudi Arabia (Alfawaz et al, 2021). A previous study shows a significant increase in physical activity including swimming and physical activity with weights during home quarantine (Alfawaz et al, 2021). The reported low number of participants who did vigorous activity during quarantine was most likely due to the dependence of their routine on gyms to keep them physically fit.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…However, the findings contraindicated the results of the previous study showing the negative effect of home quarantine on physical activity among adults in Saudi Arabia (Alfawaz et al, 2021). A previous study shows a significant increase in physical activity including swimming and physical activity with weights during home quarantine (Alfawaz et al, 2021). The reported low number of participants who did vigorous activity during quarantine was most likely due to the dependence of their routine on gyms to keep them physically fit.…”
Section: Discussioncontrasting
confidence: 75%
“…Our findings were parallel to a study conducted in France in which there were differences in levels of vigorous activities during the COVID-19 pandemic (Marchant et al, 2021). However, the findings contraindicated the results of the previous study showing the negative effect of home quarantine on physical activity among adults in Saudi Arabia (Alfawaz et al, 2021). A previous study shows a significant increase in physical activity including swimming and physical activity with weights during home quarantine (Alfawaz et al, 2021).…”
Section: Discussionsupporting
confidence: 72%
“…In addition, reports show an overall decrease in walking during COVID-19 self-quarantine [17]. Physical activity behavior data were released during the COVID-19 pandemic by Fitbit, Inc.…”
Section: Sedentary Behaviormentioning
confidence: 99%
“…The exact amount of caloric increase due to snacking is not provided in the literature. However, a commonly reported theme during COVID-19 self-quarantine is increased snacking frequency [12,15,17,33,36]. For example, crosssectional data from 1097 Poles revealed that 52% of participants admitted to snacking more frequently between meals when compared to before the pandemic [37].…”
Section: Snackingmentioning
confidence: 99%
“…For example, a cross-sectional study of 37,252 participants from France found that 63% reported increased sedentary time, with an average of seven hours per day spent sitting during lockdown [8]. In addition, reports show an overall decrease in walking during COVID-19 self-quarantine [9]. A worldwide sample of roughly 450,000 subscribers of a popular fitness app found that daily step counts were reduced by roughly 30% within 30 days of pandemic declaration [10].…”
Section: Introductionmentioning
confidence: 99%